Google Workspace Training Management to Improve the Quality of MTs Learning in Purwakarta - Ermawati, Ermawati; Latifah, Siti; Aries Sofwan Zarkasih, R.; Yasmadi, Bambang; Kartika Abbas Fauzi, Ikka (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
One of the breakthroughs made by the Ministry of Education, Culture, Research and Technology is the launch of Learning Accounts which can be accessed through www.belajar.id. This account can be used by students, educators, and education staff to access electronic-based learning services. A Learning Account is created in the form of a Google Account with the @belajar.id domain. The use of technology and mastery of digital literacy are important for teachers to master considering that currently many learning materials are sourced and accessed from the internet. This training aims to assist teachers at KKMTs Purwakarta, in accessing features available on Google Workspace for Education, so that it is hoped that teachers can maximize the student learning process online during distance learning. The general objective of implementing this training is to increase teachers' understanding and skills regarding the use of digital technology as a learning medium in learning activities. The specific objectives of this training include: (1) Teachers are able to use and manage online classes, (2) optimize available digital technology facilities, and (3) increase the effectiveness, efficiency and attractiveness of learning. The methods that will be used in the implementation of the training are socialization, practice, mentoring, and evaluation. This training material will be carried out in 2 stages where the first stage will focus more on providing information about the material regarding the role of digitizing learning media. This information is very important so that research participants get an overview of the role of digital technology as a learning medium, as well as the importance of training as a form of teacher self-development. The second stage, the training focused on introducing and understanding Google Workspace For Education, in which the training introduced the features available on Google, such as: Google Mail, Google Drive, Google Class Room, Google Meet, Jamboard, Google Calendar, Google Doc, Google Slides, Google Forms, Google Sheets, and Google Sites. Evaluation of this activity is carried out during training activities and the results of making digital learning media. The aspects that were evaluated were attendance, participant activity, participants' understanding of the material that had been given. The criteria for achieving the program for each aspect are the attendance of participants,